Coordination or Collision? The Intersection of Diabetes Care, Cybersecurity, and Cloud-Based Computing. (March 2017) - Thiel, Scott; Mitchell, Jennifer; Williams, Jim
Diagnosis and treatment of diabetes changed little from the Middle Ages through the early 19th century, when the first chemical test for the condition was developed. In the 20th century, advances in diabetes management gained momentum with home-use diagnostic devices and mass-produced insulin. In the 21st century, technological developments around diabetes are advancing so rapidly that a small, discrete system of medical devices that serve as an artificial pancreas are now possible. In this article, we assert that medical device interoperability and cyber security are necessary preconditions for safe, effective, and reliable widespread use of the artificial pancreas system.